Designing Cham Font Unicode Standard and Cham Keyboard - Nhung Buon Krong, Tuyet; Ngoc Sang, Van; Bin Bilal Ali, Mohamad (International Journal of Engineering and Technology, 2018)
The main purpose of this research is to design and develop the Cham font for Unicode standard and Cham keyboard application. Research sample is divided into two groups and research instrument distributed into three forms of survey. The Cham font Unicode standard and the Cham keyboard (Chamkey) was developed using ADDIE model. This survey, the acceptance of Cham font, and Cham keyboard view by fifty-four respondents and the results showed that 100% respondents either agreed or strongly agreed with every statement. In order to evaluate Cham font typeface, we choose fifty-four participants include academics, experts and students to evaluate the typefaces of Cham font using two forms. All of them totally agreed that the typeface of Cham fonts were designed exactly for all alphanumeric Cham letters with the result for EFEO Cam Times is 99.12% and EFEO Cam Arial is 99.64%. Viewed by sixteen experts using Fuzzy Delphi for Cham keyboard application the results show that percentage of all items are 100%, more than what required (75%), the value of d for total construct is 0.08 (required d ≤ 0.2). Thus, it can be concluded that all sixteen experts have come to a consensus that the Cham keyboard is acceptable. In order to preserve and promote the cultural heritage as well as the language and Cham scripts of the United Nations Charter on Indigenous Peoples, we offer a solution for applying information technology in the issue of preserving the native language of the Cham in Vietnam. Hence, using technologies to design and develop for Cham fonts for Unicode standard and Cham keyboards application is not only theoretically significant but also practically significant.